2019
DOI: 10.28991/cej-2019-03091323
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Differences Towards Internal and External Factors in Making the Bid/No Bid Decision

Abstract: Decision-making and subjective evaluation are two important aspects that characterizes the involvement of an organization in tender process. Moreover, selection of the right project to bid for is a principal feature of business success. The study aims to investigate the behavioral differences of Saudi construction contractors toward internal and external factors based on the process of modelling the bidding decisions. A quantitative research design is used to investigate the behavioral differences of 97 contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Mature firms have lots of experience and they had built a significant reputation in the industry. Every mature firm competes for mega projects to acquire a large profit and for developing a long-term relationship with the government but numerous mature firms experience "government pressure during bidding' because a mega project is awarded to the firm with a strong relationship with the present government (Bageis et al, 2019;Bageis & Fortune, 2009). Nonetheless, numerous mature firms are discouraged from bidding due to fear of rejection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mature firms have lots of experience and they had built a significant reputation in the industry. Every mature firm competes for mega projects to acquire a large profit and for developing a long-term relationship with the government but numerous mature firms experience "government pressure during bidding' because a mega project is awarded to the firm with a strong relationship with the present government (Bageis et al, 2019;Bageis & Fortune, 2009). Nonetheless, numerous mature firms are discouraged from bidding due to fear of rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Nirab (2007) while working on the study in the Gaza Strip identified the market related factors as being pivotal in the bidding techniques. Bageis et al (2019) concluded market value as one of the important factors affecting the bidding decisions of CCFs in Saudi Arabia. Dulaimi and Shan (2002) found availability of other projects as critical in the bid mark-up decisions of CCFs in Singapore.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations